Improved reliability of planar power interconnect with ceramic-based structure - Zhang, Hui; Li, Jianfeng; Dai, Jingru; Corfield, Martin; Liu, Xuejian; Liu, Yan; Huang, Zhengren; Johnson, Christopher Mark (IEEE, 2018)
This paper proposes an advanced Si3N4 ceramic-based structure with through vias designed and filled with brazing alloy as a reliable interconnect solution in planar power modules. Finite element (FE) modeling and simulation were first used to predict the potential of using the proposed Si3N4 ceramic-based structure to improve the heat dissipation and reliability of planar interconnects. Power cycling tests and non-destructive microstructural characterization were then performed on Si3N4 ceramic-based structures, flexible printed circuit boards (PCB) and conventional Al wire interconnect samples to evaluate the FE predictions. Both the FE simulations and experimental tests were carried out on single Si diode samples where both the ceramic-based structures and flexible PCBs were bonded on the top sides of Si diodes with eutectic Sn-3.5Ag solder joints. The results obtained demonstrate that Si3N4 ceramic-based structures can significantly improve the reliability of planar interconnects. The experimental average lifetimes and FE simulated maximum creep strain accumulations for the ceramic-based structure and flexible PCB interconnect samples can reasonably be fitted to existing lifetime models for Sn-3.5Ag solder joints. Discrepancies between the models and experimental results can be attributed to defects and poor filling of the brazing alloy in the vias through the Si3N4 ceramic.